Alternative Spirituality in Times of Pandemic - Kováčová, Viktória (Lidé města, 2023)
This work focuses on how members of the researched community – which practices alternative spirituality – live and think, for example in the field of health. The research was conducted in the Tatra Mountains in Liptov in central Slovakia. Qualitative data were obtained from the community, which is closely connected to this environment. The research sample consisted of 10 people (5 men and 5 women) who are part of the community. Most informants prefer alternative forms of medicine, such as Ayurveda, and rather reject the prevailing biomedical health system associated with the pharmaceutical industry. This inclination was also manifested during the COVID-19 pandemic, when most of them refused to be vaccinated and preferred instead to build their immunity through overcoming the given disease. They rarely, if ever, visit doctors. When they get sick, in most cases, they look for a deeper, spiritual cause and meaning of their health problems. They prefer natural nutritional supplements, herbs, and other forms of prevention. The main goal of this research was to find out how members of this community were affected by the pandemic situation, how they coped with it, and how they perceived it. I was also interested in finding out what the main source of their information was and whom they considered to be the final authority. To this end, I researched the organization of their time and daily functioning. Through the main research methods, such as in-depth interviews and participant observations, I tried to find out what led the research sample to alternative spirituality and how it is currently reflected in their lives. I assumed that alternative spirituality helps the informants to find meaning in life, as well as to understand the situations they were confronted with. I expected that these situations and experiences led them to form certain alternative life philosophies and that the research sample regarded persons who practice alternative spirituality, or hold life philosophies that they evaluate as similar to their own, as reliable sources of information.